Copper‐supported β‐cyclodextrin‐functionalized magnetic nanoparticles: Efficient multifunctional catalyst for one‐pot 'green' synthesis of 1, 2, 3‐triazolylquinazolinone derivatives. (11th January 2018) - Bahadorikhalili, Saeed; Ashtari, Arsalan; Ma'mani, Leila; Ranjbar, Parviz Rashidi; Mahdavi, Mohammad
Abstract : The green synthesis of 2‐(4‐((1‐phenyl‐1 H ‐1, 2, 3‐triazol‐4‐yl)oxy)phenyl)quinazolin‐4(3 H )‐one derivatives is reported. The catalyst for this synthesis is copper‐supported β‐cyclodextrin‐functionalized magnetic silica–iron oxide nanoparticles ([Cu@BCD@SiO2 @SPION]). [Cu@BCD@SiO2 @SPION] simultaneously catalyses 'click' reaction, oxidation of CN bond and multicomponent reaction. The desired 1, 2, 3‐triazolylquinazolinone product is easily obtained in water at room temperature under mild reaction conditions. Another advantage of the catalyst is its reusability. It can simply be isolated using an external magnet and reused in reactions with no significant decrease in catalyst efficiency. Transmission electron microscopy, scanning electron microscopy, vibrating sample magnetometry and Fourier transform infrared spectroscopy are used for exact characterization of the [Cu@BCD@SiO2 @SPION] catalyst. Abstract : A novel catalyst based on copper‐supported β‐cyclodextrin‐functionalized magnetic silica–iron oxide nanoparticles is prepared. The catalyst catalyzes 'click' reaction, CN bond oxidation, and multicomponent reaction, for the synthesis of 2‐(4‐((1‐phenyl‐1H‐1, 2, 3‐triazol‐4‐yl)oxy)phenyl) quinazolin‐4(3H)‐one derivatives. The products are prepared in water at room temperature under mild reaction conditions. Another advantage of the catalyst is its reusability, while can simply be isolated using an external magnet and reused in reactions with no significant decrease in catalyst efficiency.